Evaluation of Physical and Mechanical Properties of Structural Components of Ti-Nb Alloy; Advanced Materials Research; Vol. 1040 : High Technology: Research and Applications 2014 (HTRA 2014) - Kovalevskaya Zh. G. Zhanna Gennadievna; Khimich M. A.; Belyakov A. V.; Shulepov I. A. Ivan Anisimovich (Advanced Materials and Nanotechnology, 2014)
Title screen